2016
DOI: 10.1128/jcm.00349-16
|View full text |Cite
|
Sign up to set email alerts
|

Application of Whole-Genome Sequencing Data for O-Specific Antigen Analysis and In Silico Serotyping of Pseudomonas aeruginosa Isolates

Abstract: Accurate typing methods are required for efficient infection control. The emergence of whole-genome sequencing (WGS) technologies has enabled the development of genome-based methods applicable for routine typing and surveillance of bacterial pathogens. In this study, we developed the Pseudomonas aeruginosa serotyper (PAst) program, which enabled in silico serotyping of P. aeruginosa isolates using WGS data. PAst has been made publically available as a web service and aptly facilitates highthroughput serotyping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 37 publications
2
74
0
Order By: Relevance
“…Serotyping of P. aeruginosa was originally developed using immunochemical assays but has now been supplemented with genetic methods such as PCR and sequencing. [27,29]. We guide the reader to Lam et al [27] for a perspective on the history, benefits, and challenges of different serotyping methods in P. aeruginosa.…”
Section: Structure Of Lipid a Core And O Antigenmentioning
confidence: 99%
“…Serotyping of P. aeruginosa was originally developed using immunochemical assays but has now been supplemented with genetic methods such as PCR and sequencing. [27,29]. We guide the reader to Lam et al [27] for a perspective on the history, benefits, and challenges of different serotyping methods in P. aeruginosa.…”
Section: Structure Of Lipid a Core And O Antigenmentioning
confidence: 99%
“…Sam files generated from mapping each isolate to PAO1 were used to visualize coverage with BRIG (version 0.95) (118) and CGView (119). Sequences were compiled into de novo assemblies using SPAdes (120) through KBASE (119) for serotype prediction with PAst 1.0 (122) and strain typing with PubMLST (123). Table S1 Supplementary Data 1 R-type specificity is determined by the sequence on the foot of the tail fiber, which is believed to recognize glycosylated structures on the outer membrane (such as the LPS).…”
Section: Lps Extraction and Characterizationmentioning
confidence: 99%
“…2A), but the complete genome sequences of these two strains are unavailable. PAst analysis revealed that PA154197 belongs to the Serotype O9 (26) (Table 1). Analyzing its accessory genome identified 21 genome islands (GIs) including 3 prophages (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The multiple locus sequence type (MLST) and serotype of PA154197 was predicted based on the PubMLST database (www.pumlst.org) and the Pseudomonas aeruginosa serotyper (PAst) tool (26).…”
Section: Methodsmentioning
confidence: 99%